Targeting of EIF4EBP1 by miR‐99a‐3p affects the functions of B lymphocytes via autophagy and aggravates SLE disease progression. Issue 21 (20th October 2021) - Yang, Meng; Yang, Binbin; Deng, Danqi
Abstract: Excessive activation of immune cells plays a key role in the pathogenesis of systemic lupus erythematosus (SLE). The regulation of immune cells by miRNAs is a research hotspot. In this study, second‐generation high‐throughput sequencing revealed a reduction in miR‐99a‐3p expression in patients with SLE; however, the specific mechanism underlying this phenomenon remains unclear. After transfection with an miR‐99a‐3p agomir, the proliferation of Ball‐1 cells decreased and the levels of their apoptosis increased. The opposite effects were observed in cells transfected with the miR‐99a‐3p antagomir. Luciferase reporter assay indicated that miR‐99a‐3p directly targeted EIF4EBP1. Rescue experiments confirmed the proposed interaction between miR‐99a‐3p and EIF4EBP1. In vitro, in vivo and clinical investigations further confirmed that the miR‐99a‐3p agomir reduced the expression of EIF4EBP1, LC3B and LAMP‐2A. In the in vivo experiments, serum levels of anti‐nuclear antibodies, double‐stranded DNA, IgE, IgM, IL‐6, IL‐10 and B lymphocyte stimulator were higher in mice from the antagomir group than those in mice from the MRL/lpr group. Furthermore, the protein and mRNA levels of EIF4EBP1, LC3B and LAMP‐2A, the intensity of immunohistochemical staining of EIF4EBP1, LC3B and LAMP‐2A, the urinary protein levels, and the C3 immunofluorescence deposition increased in mice from the antagomir group. The upregulation of miR‐99a‐3p expression protected B cells from EIF4EBP1‐mediated autophagy, whilst the downregulation of miR‐99a‐3p expression induced autophagy via the EIF4EBP1‐mediated regulation of the autophagy signalling pathway in B cells isolated from individuals with SLE. Based on these results, miR‐99a‐3p and EIF4EBP1 may be considered potential targets for SLE treatment.